Cover Feature: Enhancing the Antioxidant Activity of Technical Lignins by Combining Solvent Fractionation and Ionic‐Liquid Treatment (ChemSusChem 21/2019). Issue 21 (23rd October 2019) - Majira, Amel; Godon, Blandine; Foulon, Laurence; van der Putten, Jacinta C.; Cézard, Laurent; Thierry, Marina; Pion, Florian; Bado‐Nilles, Anne; Pandard, Pascal; Jayabalan, Thangavelu; Aguié‐Béghin, Véronique; Ducrot, Paul‐Henri; et al.
Abstract : The Cover Feature shows a cascade biorefinery process for the upgrading of technical lignins and sustainable production of phenolic oligomers of interest as substitutes for commercial antioxidants. A grass soda technical lignin undergoes a process combining solvent fractionation and treatment with an ionic liquid, and a comprehensive investigation of the structural modifications is performed. More information can be found in the Full Paper by A. Majira et al. on page 4799 in Issue 21, 2019 (DOI: 10.1002/cssc.201901916 ).